Corporate governance and transaction cost economics: A study of the equity governance structure (2014)
This paper examines the Transaction Cost Economics (TCE) theory of capital structure and finds that for the case of equity the usual TCE logic is not fully worked out. In particular, an analysis of the key issue of bilateral dependency between the firm and its shareholders is absent. To fill this gap in the literature, the paper further develops the theory of the equity governance structure by taking account of the concept of bilateral dependency over the lifecycle of the firm. The paper finds that, both theoretically and empirically, contractual hazards are indeed mitigated for the case of fast growing young firms which are dependent on shareholders to finance future growth. In contrast, for the case of mature firms, which in virtue of their large free cash flows are independent from shareholders, contractual safeguards are altered to the disadvantage of shareholders and consequently managerial discretion costs increase.